Establishing a harmonized haemophilia registry for countries with developing health care systems. (17th April 2013) - Alzoebie, A.; Belhani, M.; Eshghi, P.; Kupesiz, A. O.; Ozelo, M.; Pompa, M. T.; Potgieter, J.; Smith, M.
Summary: Over recent decades tremendous progress has been made in diagnosing and treating haemophilia and, in resource‐rich countries, life expectancy of people with haemophilia (PWH) is now close to that of a healthy person. However, an estimated 70% of PWH are not diagnosed or are undertreated; the majority of whom live in countries with developing health care systems. In these countries, designated registries for people with haemophilia are often limited and comprehensive information on the natural history of the disease and treatment outcomes is lacking. Taken together, this means that planning efforts for future treatment and care of affected individuals is constrained in countries where it is most needed. Establishment of standardized national registries in these countries would be a step towards obtaining reliable sociodemographic and clinical data for an entire country. A series of consensus meetings with experts from widely differing countries with different health care systems took place to discuss concerns specific to countries with developing health care systems. As a result of these discussions, recommendations are made on parameters to include when establishing and harmonizing national registries. Such recommendations should enable countries with developing health care systems to establish standardized national haemophilia registries. Although not a primary objective, the recommendations should also help standardized data collation on an international level, enabling treatment and health care trends to be monitored across groups of countries and providing data for advocacy purposes. Greater standardization of data collation should have implications for optimizing resources for haemophilia care both nationally and internationally.